2022
DOI: 10.3390/jlpea12010014
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-Compatible Memristive Devices Tailored by Laser and Thermal Treatments

Abstract: Nowadays, memristors are of considerable interest to researchers and engineers due to the promise they hold for the creation of power-efficient memristor-based information or computing systems. In particular, this refers to memristive devices based on the resistive switching phenomenon, which in most cases are fabricated in the form of metal–insulator–metal structures. At the same time, the demand for compatibility with the standard fabrication process of complementary metal–oxide semiconductors makes it relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 66 publications
(83 reference statements)
0
5
0
Order By: Relevance
“…Figure 4 shows an HR X-TEM image of a SiO x -based memristive device after the thermal treatment. According to Figure 4 , the SiO x film has an amorphous structure with nanocrystals identified as Zr 3 O (area 1) and ZrO 2 (area 2) through a comparison of the interplanar spacings in the HR X-TEM image with the literature data performed earlier [ 8 ]. Such nanocrystals can form during thermal treatment due to a partial oxidation of the top electrode layer and can play a positive role in the localization of conductive filaments, e.g., as electric field concentrators [ 13 ].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Figure 4 shows an HR X-TEM image of a SiO x -based memristive device after the thermal treatment. According to Figure 4 , the SiO x film has an amorphous structure with nanocrystals identified as Zr 3 O (area 1) and ZrO 2 (area 2) through a comparison of the interplanar spacings in the HR X-TEM image with the literature data performed earlier [ 8 ]. Such nanocrystals can form during thermal treatment due to a partial oxidation of the top electrode layer and can play a positive role in the localization of conductive filaments, e.g., as electric field concentrators [ 13 ].…”
Section: Resultsmentioning
confidence: 95%
“…The absence of changes in R s at high frequencies indicates the absence of electrochemical processes leading to a change in resistance in the top electrode. Earlier, the thermal treatment of memristive stacks was shown to result in an irreversible change in their electrical characteristics and to positively affect the resistive switching performance of these stacks positively in some cases [8]. Because the memristive stacks under study did not demonstrate stable resistive switching in the initial state, they were subjected to thermal treatment in dried air ambient in a sealed thermostat at 250 °C for 10 min.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, laser post-treatment is very promising for modifying the performance of the memristors. Koryazhkina et al reported that using laser and thermal treatment can significantly enhance the hysteresis loop in I-V curves of SiNx-based memristors and reduce switching voltage [42]. The effects were attributed to the change of positive-charge density and the annealing of surface states.…”
Section: Introductionmentioning
confidence: 99%